Cancer‐related gene mutations and intratumoral genetic heterogeneity in human epidermal growth factor receptor 2 heterogeneous gastric cancer. Issue 11 (1st September 2020) - Kanayama, Kazuki; Imai, Hiroshi; Usugi, Eri; Matsuda, Chise; Ichishi, Masako; Hirokawa, Yoshifumi S.; Watanabe, Masatoshi
Abstract : Human epidermal growth factor receptor 2 (HER2) protein overexpression is associated with HER2 gene amplification, a critical driver oncogenetic change in gastric cancer. HER2 heterogeneity in advanced gastric cancer is associated with a poor prognosis and affects the clinical efficacy of trastuzumab. However, the mechanisms of HER2 heterogeneity are not fully understood. Here, we examined whether HER2 heterogeneous gastric cancer exhibited intratumoral genetic heterogeneity in other cancer‐related genes. Two cases of advanced gastric cancer with HER2 heterogeneity were selected, and samples of HER2‐positive and HER2‐negative areas in each case were analyzed using a cancer‐associated multiple gene panel. In both cases, TP53 mutations were observed in both HER2‐positive and HER2‐negative areas, whereas many of the potential driver and passenger mutations differed between HER2‐positive and HER2‐negative areas. Overall, our findings demonstrated that HER2 heterogeneous gastric cancer exhibited intratumoral genetic heterogeneity in other cancer‐related genes and that the molecular mechanisms could differ between HER2‐positive and ‐negative areas.